2021
DOI: 10.3390/s21165586
|View full text |Cite
|
Sign up to set email alerts
|

On the Optimization of Regression-Based Spectral Reconstruction

Abstract: Spectral reconstruction (SR) algorithms attempt to recover hyperspectral information from RGB camera responses. Recently, the most common metric for evaluating the performance of SR algorithms is the Mean Relative Absolute Error (MRAE)—an ℓ1 relative error (also known as percentage error). Unsurprisingly, the leading algorithms based on Deep Neural Networks (DNN) are trained and tested using the MRAE metric. In contrast, the much simpler regression-based methods (which actually can work tolerably well) are tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 84 publications
0
22
1
Order By: Relevance
“…We also compared three recent RGB-based spectral reconstruction methods, namely, Polynomial methods [ 18 , 26 ], RBF (Radial Basis Function) network method [ 17 ], and Gaussian Process method [ 20 ]. Sparse coding [ 1 ] and deep learning [ 19 ] methods require a lot more training samples and they are not included in this work.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…We also compared three recent RGB-based spectral reconstruction methods, namely, Polynomial methods [ 18 , 26 ], RBF (Radial Basis Function) network method [ 17 ], and Gaussian Process method [ 20 ]. Sparse coding [ 1 ] and deep learning [ 19 ] methods require a lot more training samples and they are not included in this work.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Despite in the literature DNN type SR algorithms work better (but not much better 32,33 ) than regression algorithms for seen and expected images (e.g., the ICVL datasets), our experiments show that regression‐based algorithms for spectral reconstruction work as well as their DNN counterparts for the following four scenarios: training with and testing on the SFU's MW images, training with and testing on the SFU's RMW images, training with the original ICVL hyperspectral images and testing on the ICVL's RMW set, and training with and testing on the ICVL's RMW sets. …”
Section: Introductionmentioning
confidence: 94%
“…Methods for estimating the spectral reflectance from camera signals are critical for improving measurement accuracy and detection speed. The methods can be based on basis spectra [ 17 , 18 , 19 , 20 ], Wiener estimation [ 14 , 21 , 22 ], regression [ 23 , 24 , 25 , 26 , 27 , 28 ], and interpolation [ 29 , 30 , 31 , 32 , 33 , 34 ]. The basis-spectrum methods assume that the target spectrum to be reconstructed is a linear combination of the basis spectra derived from training samples.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral reflectance image is reconstructed pixel-by-pixel using the methods in [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ], i.e., the spectrum of a pixel is reconstructed from the camera signals of the pixel. For example, the authors of [ 32 ] showed spectral reflectance images reconstructed using the LUT method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation